The early intubation of lacrimal duct in traumatic and operative lower eyelid loss and medial canthal region defects, with simultaneous reconstruction dressed by application of self constructed battlefield ophthalmic dressing - Stankiewicz, Andrzej; Witkowski, Wojciech; Różycki, Radosław; Szymański, Krzysztof (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
The treatment of acquired, imperfect drainage of tears through the lacrimal duct system in the situation of medial canthal region defect (operative or traumatic), is an important part of clinical ophthalmology and reconstructive surgery. The multidisciplinary approach to the reconstruction of all soft tissues with use of early prosthetic reconstruction and lower canalicular intubation by use of silicone tube or simple nylon thread, is the theme of the paper. The lacrimal duct repair should be performed on primarily, as well as coverage or reconstruction of skin defect. The authors compared the efficiency of simple lower canalicular intubation with use of normal surgical thread or silicone tube, with immediate medial canthal region defect plastic reconstruction. Simultaneously, the original self-constructed special battlefield ocular dressing was tested in the analyzed cases, to determine whether it is the suitable or not, in the procedure. The results were estimated on the base of clinical criteria: degree of epiphora after 6/12 weeks (subjective and evaluated accordingly to Munk score), early lacrimal obstruction/stenosis, comfort/ discomfort of patient, and utility of the military dressing (bad/good/very good). The proposed own method of simple use of nylon thread seems to be useful, particularly in traumatic damage of lower canaliculus associated with multilayer medial canthus soft tissues defects and facial bone structures impairment. In analyzed material, it was more comfortable for patients than silicone intubation and may be utilize in definitive reconstruction, as well as in temporary splinting of lacrimal system and creation of artificial lacrimal drainage through the lower canaliculus. It is useful at the battlefield conditions. The battlefield ocular dressing tested on was very high evaluated in traumatic cases and considered as good in neoplastic patients.